2017
DOI: 10.1002/jssc.201700566
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative fingerprinting based on the limited‐ratio quantified fingerprint method for an overall quality consistency assessment and antioxidant activity determination of Lianqiao Baidu pills using HPLC with a diode array detector combined with chemometric methods

Abstract: Lianqiao Baidu pills are widely used herbal medicinal preparation that were analyzed to develop a quality consistency technique. The characteristic fingerprints of 28 batches of Lianqiao Baidu pill samples were established at five wavelengths and simultaneously assessed by using a limited-ratio quantified fingerprint method using 15 marker compounds. The principal component analysis and fingerprinting results were compared, and the qualitative classification of the samples by principal component analysis agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…QFM typically uses 3 criteria to determine the quality grade of the sample: 1) qualitative similarity, which represents the similarity in the number and distribution of fingerprint peaks between the sample and reference, 2) quantitative similarity, which reflects the similarity in the overall content of the fingerprints, and 3) fingerprint variation coefficient, which represents the qualitative variation/dissimilarity of the fingerprints ( Liu et al, 2015 ). Based on how these 3 criteria are calculated, several QFMs have been reported such as the simple quantified ratio fingerprint method ( Liu et al, 2015 ), limited ratio quantified fingerprint method ( Chen et al, 2018 ), equal weight ratio quantitative fingerprint method ( Gong et al, 2021 ), linear quantitative profiling method ( Hou et al, 2019 ), averagely linear quantified fingerprint method ( Zhang et al, 2019 ), systematic quantified fingerprint method ( Lan et al, 2019 ), and average method of systematic quantified fingerprint method ( Wang et al, 2021b ).…”
Section: Applications Of Fingerprinting Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…QFM typically uses 3 criteria to determine the quality grade of the sample: 1) qualitative similarity, which represents the similarity in the number and distribution of fingerprint peaks between the sample and reference, 2) quantitative similarity, which reflects the similarity in the overall content of the fingerprints, and 3) fingerprint variation coefficient, which represents the qualitative variation/dissimilarity of the fingerprints ( Liu et al, 2015 ). Based on how these 3 criteria are calculated, several QFMs have been reported such as the simple quantified ratio fingerprint method ( Liu et al, 2015 ), limited ratio quantified fingerprint method ( Chen et al, 2018 ), equal weight ratio quantitative fingerprint method ( Gong et al, 2021 ), linear quantitative profiling method ( Hou et al, 2019 ), averagely linear quantified fingerprint method ( Zhang et al, 2019 ), systematic quantified fingerprint method ( Lan et al, 2019 ), and average method of systematic quantified fingerprint method ( Wang et al, 2021b ).…”
Section: Applications Of Fingerprinting Methodsmentioning
confidence: 99%
“…The relationship between the CE fingerprints and other properties such as biological activities can also be further investigated using PLSR ( Chen et al, 2018 ; Hou et al, 2019 ). Other chemometric methods for classification such as PCA and HCA have also been explored on CE fingerprints ( Iino et al, 2012 ; Roblová et al, 2016 ; Hou et al, 2019 ).…”
Section: Applications Of Fingerprinting Methodsmentioning
confidence: 99%
“…Approximately 0.5 ml solutions at different concentrations (0.2, 0.4, 0.8, 1.6, 2.0 mg/ml) was added to 1.5 ml DPPH solution and mixed evenly. The absorbance value was measured at 517 nm after storing the mixture at room temperature for 30 min in the dark, and quercetin was used as a positive control [31,32].…”
Section: 2-diphenyl-1-picrylhydrazyl Radical Scavenging Abilitymentioning
confidence: 99%
“…It has anti-inflammatory effects (i.e., for treatment of colds, allergies, and dermatitis) and antiatherogenic effects [1][2][3]. Recently, Chen et al [4,5] reported a high-performance liquid chromatography (HPLC)-diode array detection and micellar electrokinetic chromatography assays for quality control of Lianqiao Baidu pills (LBP). In China, LBP is used for the treatment of diseases similar to those treated by YPS in Korea [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chen et al [4,5] reported a high-performance liquid chromatography (HPLC)-diode array detection and micellar electrokinetic chromatography assays for quality control of Lianqiao Baidu pills (LBP). In China, LBP is used for the treatment of diseases similar to those treated by YPS in Korea [4,5]. However, LBP is a completely different herbal formulation, consisting of 19 herbal medicines [6].…”
Section: Introductionmentioning
confidence: 99%